Squatting in American Culture: A Study on James Fenimore Cooper’s Novel The Prairie - Riyatno Riyatno; Asih Ernawati (Universitas Sebelas Maret, 2022)
The history of America cannot be separated from squatting. When European people came to the eastern coast of America in 1600s, they had lived in the settlement that did not belong to them. They did not stop living in the settlement, rather, they kept moving to the West to look for better life. The discovery of gold in California made them move to the West although they underwent difficulties along their journey. This study attempts to explore squatting in American culture in James Fenimore Cooper’s novel The Prairie. This research uses Cultural Studies method, in which literary, historical and sociological approaches are combined to analyse a certain phenomenon on a text. History and sociology are used in the research because they complement the existing sources in the literature. The data are mainly taken from James Fenimore Copper’s novel, namely, The Prairie. The novel is used in the research as starting points to describe squatting, and then the development of it can be described in American Culture. Other data are taken from film, magazines, newspapers and historical and sociological articles, as well as articles from American Studies Journal. Based on the research, squatting emerges because the squatters do not have enough money to buy or to rent the land for their settlement. Besides, the squatters usually assume that the land that belongs to Indians can be occupied or owned without having to pay it.